TI_GERICHTE 11.2014.14 vom 25. Juli 2016 , Protezione della personalità: provvedimenti cautelari nei confronti di mass media - TI Tribunale d'appello (2016)
Protezione della personalità: provvedimenti cautelari nei confronti di mass media